Associations of Central Auditory Processing With Brain Volumes. (17th December 2021) - Coresh, Josef; Hayden, Kathleen; Jack, Clifford; Mosley, Thomas; Pankow, James; Lin, Frank; Deal, Jennifer; Jiang, Kening
Abstract: We investigated the cross-sectional associations of speech-in-noise performance with magnetic resonance imaging brain volumes among 588 cognitively normal participants (77±4 years, 56% female) from the Aging and Cognitive Health Evaluation in Elders Study (randomized trial embedded in the Atherosclerosis Risk in Communities (ARIC) Study) baseline in 2018-19 (N=427, with hearing loss) and ARIC (N=161, normal hearing) Visit 6/7 in 2016-17/2018-19. Central auditory processing was measured by Quick Speech-in-Noise (QuickSIN) test; range: 0 to 30, lower scores=worse performance. In models adjusted for demographic and disease covariates, every 5-point decrease in QuickSIN score was associated with smaller volumes of the temporal lobe overall (-0.07SD, 95% CI:-0.13, -0.01) as well as subregions including but not limited to those important for auditory processing (amygdala:-0.13SD, 95% CI:-0.21, -0.04; middle temporal gyrus:-0.08SD, 95% CI:-0.15, -0.00; superior temporal gyrus:-0.08SD, 95% CI:-0.15, -0.01). Further research is needed to understand the mechanisms underlying these observed associations.